Measuring Cardiovascular Disease Risk Perception: Translation and Validation of the Indonesian ABCD Risk Questionnaire - Septa Meriana Lumbantoruan; Deby Kristiani Uligraff; Eva Berthy Tallutondok (Nursing Research and Practice)
Background. Cardiovascular diseases (CVDs) are still increasing worldwide contributing to increasing death worldwide. To test CVDs’ awareness, the Attitude and Belief about Cardiovascular Disease (ABCD) questionnaire was developed. However, this questionnaire is not available in Indonesia language. Methods. The original questionnaire was translated in both directions forward and backward. The process is then continued with a content validity index created by three experts. The exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) then determine the factors that support the translated questionnaire. The splitting sample method was applied in both factor analyses. Internal consistency testing of 18 items was performed on 236 samples. Result. The validity of the entire questionnaire subscale was satisfactory. Three retained factors were supported by the EFA and CFA, namely, risk perception, perceived benefit, and healthy eating intention. The internal consistency was acceptable based on Cronbach alpha and ordinal alpha. The Indonesian version of ABCD questionnaire was statistically valid and reliable to be used. Conclusion. The Indonesian version of the ABCD questionnaire is a valid questionnaire to access the attitude and belief of CVDs in Indonesia.